THE POWER OF UKRAINE’S PRESIDENT: PERSONAL PRONOUNS ON ZELENSKY’S SPEECH - Dian Luthfiyati; Fitria Nur Hamidah (University of Muhammadiyah Malang, 2022)
This study analyzes how Zelensky used first-person personal pronounsin his political speeches. This study discussed about the occurrences offirst personal pronouns in political speeches by using qualitativemethodologies, that is document study to identify their forms anddiscourse function. The results showed that The first personal pronounsare identified in discovered of Zelensky’s speeches. The first personalpronouns used in Zelensky addresses were pronoun “I”, “You”, and “We”.Zelensky used the singular personal pronoun ‘‘I’’ to express his heartfeltgratitude and admiration, as well as his professional and personalexperiences, arguments, perspectives, aspirations, and commitment. Theusage of inclusive “You” and variants indicate Zelensky 's willingness toshare responsibility, foster unity, equality, and public declarations abouttheir current situation and any potential future challenges. Usingexclusive “We” which demonstrated by Zelensky also was to show hispolitical intentions, commitment, political experiences during theelection, and significant concern for reconciliation.